A new CoFe1.9Li0.1O4 spinel oxide cathode for proton-conducting solid oxide fuel cells. Issue 22 (15th November 2022) - Yang, Xuan; Xu, Yangsen; Yu, Shoufu; Bi, Lei
Abstract: A new spinel oxide CoFe1.9 Li0.1 O4 (CFLO) has been synthesized as a cathode material for proton-conducting solid oxide fuel cells. CFLO has good structure stability up to 900 °C. In addition, the material can survive in both CO2 and steam-containing atmospheres. Compared with the Li-free sample, the Li-doping strategy significantly regulates the material's electronic structure. The low valence of Li leads to the increased amount of Fe and Co cations with higher valences. Furthermore, doping Li creates more oxygen vacancies at the material surface, which benefits the oxygen reduction reaction (ORR). The improved cathode performance for CFLO has been demonstrated that a cell using CFLO cathode reaches a peak power density of 1052 mW cm −2 at 700 °C. The cell performance is 60% larger than the Li-free cell, and similar results can be detected at other testing temperatures. In addition, the CFLO cell shows good long-term stability in the working condition. This study proposes the Li-doping strategy to modify spinel oxides and also provides a new spinel oxide as a high-performing cathode for H–SOFCs.